Pore Fluid Pressure Development in Compacting Fault Gouge in Theory, Experiments, and Nature. Issue 1 (18th January 2018) - Faulkner, D. R.; Sanchez‐Roa, C.; Boulton, C.; den Hartog, S. A. M.
Abstract: The strength of fault zones is strongly dependent on pore fluid pressures within them. Moreover, transient changes in pore fluid pressure can lead to a variety of slip behavior from creep to unstable slip manifested as earthquakes or slow slip events. The frictional properties of low‐permeability fault gouge in nature and experiment can be affected by pore fluid pressure development through compaction within the gouge layer, even when the boundaries are drained. Here the conditions under which significant pore fluid pressures develop are analyzed analytically, numerically, and experimentally. Friction experiments on low‐permeability fault gouge at different sliding velocities show progressive weakening as slip rate is increased, indicating that faster experiments are incapable of draining the pore fluid pressure produced by compaction. Experiments are used to constrain the evolution of the permeability and pore volume needed for numerical modeling of pore fluid pressure build up. The numerical results are in good agreement with the experiments, indicating that the principal physical processes have been considered. The model is used to analyze the effect of pore fluid pressure transients on the determination of the frictional properties, illustrating that intrinsic velocity‐strengthening behavior can appear velocity weakening if pore fluid pressure is not given sufficient time to equilibrate. The results illustrate that care must be taken when measuring experimentally the frictional characteristics of low‐permeability fault gouge. The contribution of compaction‐induced pore fluid pressurization leading to weakening of natural faults is considered. Cyclic pressurization of pore fluid within fault gouge during successive earthquakes on larger faults may reset porosity and hence the capacity for compaction weakening. Key Points: Pore fluid overpressure may develop in low‐permeability fault gouges during shear‐enhanced compaction The mechanical effect of pore fluid overpressures is characterized in experiments and modeled numerically Compaction weakening is important to consider in experiments and may have a first‐order influence on the mechanical behavior of faults in nature